Effects of an Engaging Process-Genre Approach on Student Engagement and Writing Achievements. Issue 5 (3rd September 2022) - Rahimi, Muhammad; Zhang, Lawrence Jun
Abstract: Exploring students' experiences with instructional approaches and learning environments is of paramount significance, as students' experiences influence their engagement and achievements. To this end, 148 students' experiences with an engaging process-genre approach to research writing were explored to document their engagement with the approach and factors influencing their engagement and to examine whether students' writing quality improved significantly. Students' narratives, the researcher's reflective journals, and students' pretest and posttest scores on the Introduction part-genres were collected and analyzed through thematic analyses and a paired samples t -test. Our findings identified facilitators and indicators of student engagement with the approach and showed that students assisted each other agentively not only in doing the activities but also in sustaining engagement in and beyond the classroom. Students attributed their sustained engagement and achievements to observing the negotiated norms, to the teaching-learning cycle of the engaging process-genre approach, and to the teacher's kindness, patience, and professional advice. These findings highlight the significance of learning experiences and suggest that teachers should consider adopting the engaging process-genre approach to establish negotiated norms, routines, and roles to trigger and sustain students' engagement with learning-to-write activities and writing.